2019
DOI: 10.1016/j.celrep.2019.09.054
|View full text |Cite
|
Sign up to set email alerts
|

PCNA Deubiquitylases Control DNA Damage Bypass at Replication Forks

Abstract: Graphical AbstractHighlights d Ubp10 and Ubp12 DUBs remove ubiquitin from PCNA K164 with distinct chain preferences d Fork association of Ubp10, but not Ubp12, depends on PCNA binding to lagging strands d PCNA-DUBs counteract template switch and Rev1 TLS factor binding to replication forks d Ubp10-and Ubp12-mediated PCNA K164 deubiquitylation promotes processive DNA replication SUMMARY DNA damage tolerance plays a key role in protecting cell viability through translesion synthesis and template switching-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 82 publications
3
43
1
Order By: Relevance
“…PCNA is ubiquitinated in response to DNA damage, but the level of ubiquitination generally observed (our study and ( 16 )) is rather low, with free-PCNA remaining predominant. Even in the absence of deubiquitylases, free-PCNA remains highly majoritarian ( 34 ). Given the low level of PCNA ubiquitination that is generally observed for S. cerevisiae , we can hypothesize that de novo ubiquitination occurs at each encounter with a lesion.…”
Section: Discussionmentioning
confidence: 99%
“…PCNA is ubiquitinated in response to DNA damage, but the level of ubiquitination generally observed (our study and ( 16 )) is rather low, with free-PCNA remaining predominant. Even in the absence of deubiquitylases, free-PCNA remains highly majoritarian ( 34 ). Given the low level of PCNA ubiquitination that is generally observed for S. cerevisiae , we can hypothesize that de novo ubiquitination occurs at each encounter with a lesion.…”
Section: Discussionmentioning
confidence: 99%
“…This rapid deubiqui>na>on could explain the low level of PCNA ubiqui>na>on generally observed upon genotoxic stress (this study and ( 16)). Indeed, the level of Ub-PCNA increases when the deubiquitylases are inac>vated (32).…”
Section: Discussionmentioning
confidence: 99%
“…The role of ubiquitin and SUMO modifications in DNA replication has been reviewed [162]. TLS-mediated DNA synthesis is downregulated and prevented at replication forks through PCNA deubiquitylation, most likely as a consequence of low TLS fidelity [163]. Significantly, it has been shown that PCNA ubiquitylation can operate after bulk genome replication, and, therefore, TLS DNA polymerases can effectively promote the error-prone DNA synthesis of ssDNA tracks late in G2 [164,165].…”
Section: Dna Synthesis Of Under-replicated Dna Tracks Prior To Mitosismentioning
confidence: 99%